Implementasi Augmented Reality Media Pengenalan Hardware Dengan Metode Multimedia Development Life Cycle Dan Prototype - Melinia Dini Afrian; Pradana Ananda Raharja (Jurnal Inovtek Polbeng Seri Informatika, 2022)
Learning activities at SD Islam Plus Masyithoh that teachers apply tend to be conventional, as in the introduction of computer hardware. The learning requires teaching aids to improve students' understanding, but the limited facilities make it difficult for students to understand computer hardware. Augmented Reality technology can provide a solution by applying markers as targets to visualize computer hardware into 3D objects in the system using the Multimedia Development Life Cycle and Prototype software development methods. This method uses the black box testing method to develop multimedia software systems in testing the application. The results obtained from BlackBox testing show that all application features' functions can run well. Then usability testing with the System Usability Scale method. The data taken are 30 samples of questionnaire data that 4th-grade students have filled out. In the test obtained, the average value of SUS is 83.1. So it can interpretation that the application testing receives a grade of "B" with the predicate "Excellent", and the conclusion in the Acceptability Ranges category is "High", with a high range of user acceptance of the application.